Considering Research Outcomes as Essential Tools for Medical Education Decision Making. (November 2015) - Miller, Karen Hughes; Miller, Bonnie M.; Karani, Reena
Abstract : As medical educators face the challenge of incorporating new content, learning methods, and assessment techniques into the curriculum, the need for rigorous medical education research to guide efficient and effective instructional planning increases. When done properly, well-designed education research can provide guidance for complex education decision making. In this Commentary, the authors consider the 2015 Research in Medical Education (RIME) research and review articles in terms of the critical areas in teaching and learning that they address. The broad categories include (1) assessment (the largest collection of RIME articles, including both feedback from learners and instructors and the reliability of learner assessment), (2) the institution's impact on the learning environment, (3) what can be learned from program evaluation, and (4) emerging issues in faculty development. While the articles in this issue are broad in scope and potential impact, the RIME committee noted few studies of sufficient rigor focusing on areas of diversity and diverse learners. Although challenging to investigate, the authors encourage continuing innovation in research focused on these important areas.